Current status of Tele-speech language therapy by type and support for patients with post-stroke aphasia: A scoping review - Yuhei Kodani; Shinsuke Nagami; Ayaka Yokozeki; Shinya Fukunaga; Katsuya Nakamura; Hikaru Nakamura (PLoS ONE, 2025)
Purpose The purpose of this study was to classify and analyze trends in the assessment and training methods used in telepractice speech-language therapy (Tele-SLT) for people with aphasia (PWA), according to the type of Tele-SLT (synchronous, asynchronous, or combined). This study particularly aimed to identify gaps that prevent the establishment of Tele-SLT, a field that has gained significant attention post-COVID-19 pandemic. Design A scoping review was conducted following the PRISMA-ScR guidelines. Setting and participants Included were research articles on Tele-SLT for individuals aged 18 years or older diagnosed with post-stroke aphasia. Articles in both English and Japanese were reviewed, using five online databases (Medline, Embase, PsycInfo, Cochrane Library, and ICHUSHI Web). Methods Studies involving Tele-SLT were categorized by support methods, content, study design, and outcomes. The quality of the extracted studies was also assessed. We also assessed the quality of the selected studies and performed a meta-analysis of some of the results. Results Of the initial 1,484 articles, 35 met the eligibility criteria. Regarding Tele-SLT support methods, 3 articles (8.57%) focused on assessment methods, while 32 (91.43%) focused on training methods. Fourteen articles (40.00%) employed synchronous Tele-SLT delivery, 20 (57.14%) employed asynchronous delivery, and 1 (2.86%) employed a combined approach. The methodological quality of 27 (77.14%) of the included Tele-SLT articles was rated as ‘Low’. A meta-analysis of randomized controlled trials on Tele-SLT demonstrated that asynchronous training was effective for language function Conclusions and significance This study highlights the need for more research, particularly on remote assessment and synchronous training methods, in Tele-SLT for PWA. Furthermore, this study emphasizes the need for improved research methodologies in this area. To provide high-quality support for PWA who have faced challenges accessing in-person speech-language therapy since the COVID-19 pandemic, further research and development of Tele-SLT implementation guidelines are needed